Religious instruction and self-esteem of deaf and hard of hearing adolescents - Sanchez, Clarissa M. (College of Education, University of the Philippines Diliman, 2019)
The aim of this study was to find out how religious instruction affects the self-esteem of the D/Hh adolescents. The study is quantitative and qualitative in nature, and used a single group pre-test and post-test design. There were a total of 38 D/Hh adolescents that participated in this study. The study was conducted in two schools which followed auditory-oral and manual/total communication approach. The religious instruction program implemented was researcher-made and is composed of eight modules. The modules focused on the Catholic teachings on God's love. The quantitative data were collected from the pre-test post-test results from the Global Self-Worth of the self-perception profiles formulated by Susan Harter. While, the qualitative data was based on class discussions and researcher's recollection of what transpired. The results showed that there was a significant increase in the self-esteem of the D/Hh participants from the Manual Communication group.